Ultrafast Sub-100 fs All-Optical Modulation and Efficient Third-Harmonic Generation in Weyl Semimetal Niobium Phosphide Thin Films - Tilmann, Benjamin; Pandeya, Avanindra Kumar; Grinblat, Gustavo; Menezes, Leonardo De S.; Li, Yi; Shekhar, Chandra; Felser, Claudia; Parkin, Stuart S. P.; Bedoya-Pinto, Amilcar; Maier, Stefan A. (Advanced Materials, 2022)
Since their experimental discovery in 2015, Weyl semimetals have generated a large amount of attention due their intriguing physical properties that arise from their linear electron dispersion relation and topological surface states. In particular, in the field of nonlinear (NL) optics and light harvesting, Weyl semimetals have shown outstanding performances and achieved record NL conversion coefficients. In this context, the first steps toward Weyl semimetal nanophotonics are performed here by thoroughly characterizing the linear and NL optical behavior of epitaxially grown niobium phosphide (NbP) thin films, covering the visible to the near-infrared regime of the electromagnetic spectrum. Despite the measured high linear absorption, third-harmonic generation studies demonstrate high conversion efficiencies up to 10−4% that can be attributed to the topological electron states at the surface of the material. Furthermore, nondegenerate pump–probe measurements with sub-10 fs pulses reveal a maximum modulation depth of ≈1%, completely decaying within 100 fs and therefore suggesting the possibility of developing all-optical switching devices based on NbP. Altogether, this work reveals the promising NL optical properties of Weyl semimetal thin films, which outperform bulk crystals of the same material, laying the grounds for nanoscale applications, enabled by top-down nanostructuring, such as light-harvesting, on-chip frequency conversion, and all-optical processing.
CRIS-Team Scopus Importer:2022-04-14
Keywords: nonlinear optics; pump–probe spectroscopy; thin films; ultrafast optics; Weyl semimetals